2016
DOI: 10.4038/sljid.v6i2.8112
|View full text |Cite
|
Sign up to set email alerts
|

Community acquired pneumonia due to Legionella pneumophila in a tertiary care hospital

Abstract: Introduction: Legionella pneumophila can cause severe community acquired pneumonia which may be life threatening. This organism is found in aquatic environments and infection is acquired through inhalation of aerosols. Few studies conducted in Sri Lanka have confirmed the presence of this organism in cooling tower water in Sri Lanka. Published data regarding human cases of legionellosis in Sri Lanka is not available. Objective: To determine the prevalence of community acquired pneumonia due to L. pneumophila a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
1
1
Order By: Relevance
“…An Indian study revealed 17.69% antigenuria, 27.43% seropositivity and no culture positivity (Javed et al 2010). A recent Sri Lankan research too did not yield legionella from culture or urinary antigen (Dissanayake et al 2016). Similarly, the current study did not find positive results in spite of combining culture with urinary antigen detection.…”
Section: Althoughcontrasting
confidence: 54%
See 1 more Smart Citation
“…An Indian study revealed 17.69% antigenuria, 27.43% seropositivity and no culture positivity (Javed et al 2010). A recent Sri Lankan research too did not yield legionella from culture or urinary antigen (Dissanayake et al 2016). Similarly, the current study did not find positive results in spite of combining culture with urinary antigen detection.…”
Section: Althoughcontrasting
confidence: 54%
“…First isolation of Legionella pneumophila in Sri Lanka was from environmental water samples and revealed positive from 57.4% of selected hotels and 38.4% of selected cooling towers (Wahala & Wickramasinghe 2000). Further, a study enrolling 80 patients with CAP in a tertiary care hospital in the country did not reveal any case of legionella (Dissanayake et al 2016). Similarly, the current study did not find a single case of legionella infection in the study group.…”
Section: Althoughsupporting
confidence: 44%
“…L. pneumophila was not identified in their study population. 8 A study done by Kottahachchi et al in the Western Province of Sri Lanka also did not identify L. pneumophila in a sample of patients with atypical pneumonia. 9 According to the results of these studies L. pneumophila has been reported from the environment and humans.…”
Section: Discussionmentioning
confidence: 91%